Análise do discurso e vitimologia: memória(s) de tráfico de drogas - Nascimento, Lucas do (Universidade Federal de São Carlos, 2011)
This study has it s center in the relevance of the discourse in all social practices. Among these, are found the judicial practice, regulationed by laws, penal, civil and criminal codes that try regulation the most of social relations. Considering the drugs traffic crime, the objective of this work it is comprehend individual-position in the process of (des) construction of juridical individual (counsel), in penal process concluded with the absolution from one of the fouler defendant. Standing in the discourse formulation´s level (and/or of constitution), we work the argumentation from of the historical-discursive process where the position of counsel individual (lawyer) is formed, it enabling motions of reading/interpretation. The corpus of analysis is formed by the decision acórdão conceded by the Justice Court of Porto Alegre, Rio Grande do Sul. This corpus exposes the practice of narcotic traffic of 3 young (the age between 20-30), whose crime happened in a gaúcha city, in 2003. In the judicial discursive practices, the purpose of the counsel s discourse is give an answer to the problem of the defendant with the purpose of absolution. This answer it seems to situated, many times, in an illusory perspective of completeness in the language, be rational and close, thinking on this way, be resolving the case/fact. To the discursive reflexion, resort on works from the french philosopher Michel Pêcheux and Michel Foucault. It is on the lard of various knowledge areas, like Discourse Analyses, Philosophy and Law that this work proposes the theorical-discursive reflexion. We observed the following considerations: 1) the activation of the Registrar of discourse memory in the fabric of criminal fact, 2) the operation of the senses, the comparison of the utterances of the defendants from the Criminal Investigation conducted by the Public Defender, 3) the s sdr defendant's "Z" built statements wish absolution: a) pick up only / just a ride, and b) real part in the imputation that he was being made, thus the formulation functioned as an effect of truth, 4) the Insurgency in sdr the Public Defender and Appellate of the subject showed that the FD has led to the authorization of the acquittal of the accused "Z" and impeded discourses of guilt and punishment, listed in determination of conviction in Judgement, and 5) the Public Defender Brazilian made discourses constituting meanings of victimology, thereby weakening mechanisms of criminology.
Discourse analyses and victimology: memoirs of narcotic traffic
Keywords: Análise do discurso; Sujeito; Vitimologia; Criminologia; Tráfico de drogas; Posição-sujeito; Discurso; Defensor público; Individual-position; Discourse; Public counsel; Victimology; Narcotic traffic; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA